Research on Random Access Technology of Inter-Frame Interference Cancellation for 6G Satellite Internet of Things - Yu XU; Qing GUO (天地一体化信息网络)
In 6G, one of the important application scenarios is ultra-massive machinetype communications, which is mainly oriented to the application scenarios of concurrent access of massive terminals such as the satellite Internet of Things.How to design an access mechanism that can meet the concurrent access service requirements of large-scale users in machine communication scenarios for the future 6G satellite communication network is an important problem to be solved.A random access protocol based on intra-frame interference cancellation was proposed.In this protocol, each access user who needs to transmit data sends multiple packet copies in one frame, and the receiver can successfully receive packets from multiple users in confl icting time slots by using interference cancellation algorithms in the frame.Compared with the traditional random access mechanism, this mechanism can greatly improve the throughput performance in the scenario of multi-user concurrent access.